2020
DOI: 10.1039/c9fo02732g
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal effects of Peruvian maca (Lepidium meyenii): a review

Abstract: Peruvian maca (Lepidium meyenii) is a root native to the Andean region, cultivated for at least 2000 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 49 publications
0
36
0
3
Order By: Relevance
“…Antimicrobial agents with repurposing potential against viral diseases, such as teicoplanin, ivermectin, itraconazole, and nitazoxanide, have been described [35]. Considering this, compounds isolated from Smallanthus sonchifolius (commonly called Yacon), a plant of the family Asteraceae, native to the Andean regions, that has been studied against colon cancer, diabetes, and obesity [36], and Lepidium meyenii (commonly called Maca), a root native to the Andean region, that has shown neuroprotective effects, antidepressant, antioxidant, anticancer, and anti-inflammatory activities [37] were searched in the Pub-Chem, Drug-Bank and ChEMBL databanks. In this regard, it was possible to find 14 and 26 compounds described from S. sonchilofolius (Table 1) and L. meyenii (Table 2), respectively.…”
Section: Literature Searchmentioning
confidence: 99%
“…Antimicrobial agents with repurposing potential against viral diseases, such as teicoplanin, ivermectin, itraconazole, and nitazoxanide, have been described [35]. Considering this, compounds isolated from Smallanthus sonchifolius (commonly called Yacon), a plant of the family Asteraceae, native to the Andean regions, that has been studied against colon cancer, diabetes, and obesity [36], and Lepidium meyenii (commonly called Maca), a root native to the Andean region, that has shown neuroprotective effects, antidepressant, antioxidant, anticancer, and anti-inflammatory activities [37] were searched in the Pub-Chem, Drug-Bank and ChEMBL databanks. In this regard, it was possible to find 14 and 26 compounds described from S. sonchilofolius (Table 1) and L. meyenii (Table 2), respectively.…”
Section: Literature Searchmentioning
confidence: 99%
“…It has been used in traditional folk medicine for generations to cure physical issues including anaemia, fertility, hormone imbalances, and menopausal symptoms like decreased sex desire, mood swings, and vaginal dryness. 83 A small number of studies have found that maca is more effective than a placebo at increasing sex desire and reducing psychological symptoms like anxiety and despair. Although no serious side effects have indeed been reported, there is a scarcity of safety information.…”
Section: Lepidium Meyenii (Maca)mentioning
confidence: 99%
“…This interest has established Maca as one of the flagship products of Peru, being sold as powder, pills, capsules, flour, liquor, and extracts at a variety of retail outlets such as health food stores and smoothie shops. 1 The Maca root, native to the Peruvian Andean region is botanically a member of the Brassicaceae family, growing in high altitude region, characterized by extreme weather conditions as rocky formations, intense sunlight and strong winds. [2][3][4][5][6] There are diverse varieties according to the color of the hypocotyl, and many Maca root-based food supplements of different colors are available on the world market due to the possible effect on the treatment of a wide range of diseases and medical disorders.…”
Section: Introductionmentioning
confidence: 99%